THEORETICAL AND CONCEPTUAL APPROACHES TO THE DEVELOPMENT OF A GREEN MARKETING STRATEGY OF ENTERPRISES (Marketing Journal, 2026)
This article explores the theoretical foundations and conceptual approaches to developing green marketing strategies for enterprises. The study analyzes contemporary interpretations of green marketing within the frameworks of stakeholder theory, the Triple Bottom Line concept, and the Sustainable Development Goals (SDGs). The article systematically reviews the elements of the green marketing mix (4P): green product, green price, green place (distribution), and green promotion. As a result, a step -by-step me thodology for implementing a green marketing strategy for companies is developed.
Keywords: green marketing; sustainable development; stakeholder theory; marketing mix; ecological strategy; corporate social responsibility; ESG. № 1 -SON YANVA R; 202 6-YIL 141